Multi-Level Integrated Adaptation Governance Workshop - Accra, Ghana. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The Systemic Integrated Adaptation (SIA) Research Program draws together diverse forms of knowledge generation and sense-making from across disciplines, sectors and social worlds towards the interrelated goals of climate adaptation, sustainable development, environmental management and food security. The SIA team welcomed decision makers in climate change adaptation from multiple levels (village, district, regional and national) to the Multi-Level Integrated Adaptation Governance Workshop, which ran April 14th to April 16th 2014 at Ghana Institute of Management and Public Administration (GIMPA), Accra, Ghana. The participants traveled from Orbili, Lawra, Wa, Tamale and from all over Accra to come together and share with each other their lives to create a mutual and comprehensive understanding of the processes involved in climate change adaptation. From this highlighting the hindrances to the processes, and possible solutions and improvements. Photos: A. Ademiluyi and E. van de Grift.